2012
DOI: 10.1186/1749-8090-7-125
|View full text |Cite
|
Sign up to set email alerts
|

How I do it – sole innominate cannulation for acute type A aortic dissection

Abstract: We describe sole direct innominate cannulation for arterial return for establishing both cardiopulmonary bypass and selective antegrade cerebral perfusion in the repair of acute type A dissection and compare it with femoral, axillary, direct aortic and apical cannulations. We believe innominate cannulation has all the advantages of right axillary cannulation and none of its disadvantages. It can be used in all patients in whom innominate artery is not dissected, obstructed, calcified or otherwise diseased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Both IA and RAA aid in avoiding retrograde perfusion of the thoracoabdominal aorta and thus reducing the risk of brain embolic and malperfusion . In the comparative studies that used both the RAA and IA, it was demonstrated that major outcomes including in‐hospital mortality, neurological complications, and major organ complications were comparable between the two methods (Table ).…”
Section: Discussionmentioning
confidence: 98%
“…Both IA and RAA aid in avoiding retrograde perfusion of the thoracoabdominal aorta and thus reducing the risk of brain embolic and malperfusion . In the comparative studies that used both the RAA and IA, it was demonstrated that major outcomes including in‐hospital mortality, neurological complications, and major organ complications were comparable between the two methods (Table ).…”
Section: Discussionmentioning
confidence: 98%
“…This sequence of staggered rupture prevented sudden exsanguination. We performed an interposition graft replacement of ascending aorta and hemiarch employing unihemispherical antegrade selective cerebral perfusion (ASCP) at 17 C using sole innominate cannulation for establishing both cardiopulmonary bypass and providing ASCP, a technique we described earlier for bi-hemispherical ASCP in root and arch replacement in bovine arch variant anatomy in 2009 (33) and uni-hemispherical ASCP in acute type A dissection repair in patients with normal anatomy (34).…”
Section: Discussionmentioning
confidence: 99%
“…One patient died [12]. With increasing use of innominate artery for arterial cannulation during surgery of the thoracic aorta [36] and during repair of type A dissection for both arterial return and selective cerebral perfusion to improve neurological outcomes [37], it is possible there might be an increase in iatrogenic innominate artery injuries. However, most cases of supra-aortic aneurysms are asymptomatic and embolization as opposed to rupture represents the greatest risk to the patient.…”
Section: Discussionmentioning
confidence: 99%